불안민감성이 대처 동기를 통해 니코틴 의존도에 미치는 영향 - 김유진 (The Graduate School, Ajou University, 2024)
본 연구는 불안민감성과 니코틴 의존도의 관계에서 대처 동기의 매개효과와 성별 및 불면증의 조절효과 및 조절된 매개효과가 있는지 확인하였다. 이를 위해 니코틴이 함유된 담배를 매일 5개비 이상 피우는 흡연자 400명을 대상으로 설문을 실시하였다. SPSS PROCESS Macro를 사용하여 불안민감성이 니코틴 의존도와 대처 동기에 각각 미치는 영향을 살펴보았을 뿐 아니라, 매개효과, 조절효과, 조절된 매개효과까지 분석하였다. 연구 결과, 대처 동기는 불안민감성과 니코틴 의존도의 관계를 부분매개하였다. 불안민감성과 대처 동기의 관계에서 성별의 조절효과는 남성에서만 유의하였다. 그리고 불안민감성과 성별 중 남성의 상호작용 효과에 의해 조절된 대처 동기는 니코틴 의존도에 영향을 미쳐 성별의 조절된 매개효과가 유의하였다. 그러나 대처 동기와 니코틴 의존도 의 관계에서 불면증의 조절효과는 유의하지 않았다. 끝으로 본 연구의 제한점과 후속 연구의 향방을 논의하였다.|This study examined whether a mediation effect of coping motives existed between anxiety sensitivity and nicotine dependence, as well as the moderation and moderated mediation effects of sex and insomnia. A survey was conducted with 400 smokers who smoke five or more cigarettes containing nicotine daily. Using the SPSS PROCESS Macro, we analyzed whether anxiety sensitivity affects nicotine dependence and coping motives, as well as whether mediation, moderation, and moderated mediating effects exist. The results indicated that coping motives partially mediated the relationship between anxiety sensitivity and nicotine dependence. The moderation effect of sex between anxiety sensitivity and coping motives was significant only for males. Additionally, coping motives, moderated by the interaction of anxiety sensitivity and male gender, affected nicotine dependence, making the moderated mediating effect of sex significant. However, the moderation effect of insomnia was not significant between coping motives and nicotine dependence. Finally, the study discussed its limitations and provided directions for future research.
학위논문(석사)--심리학과,2024. 8
Keywords: 니코틴 의존도; 대처 동기; 불면증; 불안민감성; 성별